A robust optimised shunted electrodynamic metamaterial for multi-mode vibration control. (9th June 2022) - Singleton, Lawrence; Cheer, Jordan; Daley, Steve
Abstract: This paper presents a design approach for a shunted electrodynamic metamaterial (EDMM) for broadband robust vibration control. A unit cell of 12 inertial electrodynamic transducers is proposed, where the response of each transducer is tuneable via a connected resistive and inductive shunt circuit. The variations in the parameters of an off-the-shelf transducer are characterised experimentally, before the effect of this variation on the shunted response is investigated. It is shown that instability of the system is a limiting design factor. A problem is proposed whereby the resistive and inductive shunt values of an EDMM attached to a parametrically uncertain structure are to be found, and given the complexity of the design problem, a Particle Swarm Optimisation (PSO) is utilised to find a solution using an analytical model of the system. The results of the optimisation show that the effects of uncertainty in the actuators must be included, otherwise, the solution can be unstable. However, it is also shown that it is sufficient to ignore the uncertainty in the structure and optimise the EDMM considering actuator uncertainty alone, since the EDMM motion is then highly damped and, therefore, inherently robust to structural uncertainties. Highlights: A shunted electrodynamic metamaterial for robust vibration control is proposed. The parametric variation in a specific electrodynamic transducer is characterised. The shunt impedances are optimised for attenuation of structural vibration using a particle swarm optimisation (PSO). The actuator uncertainty is the main limitation of the proposed design. Robustness to structure and transducer uncertainty is achieved.